Ladybird Histories :The Vikings - Senker,Cath
Ladybird Histories is a series of books about periods and people in history that children find especially engaging and that are often taught in schools. Each book is packed full of interesting and entertaining details that will delight all readers—from lifestyles, battles and important characters, to the influence of the past on the world around us today. Ancient Greeks is the ideal homework help book for primary school children. Packed with everything they need to know about life in ancient Greece, this book is perfect for all school project work. It is packed with information about topics such as what the ancient Greeks wore, what they ate and who their leaders were.